2020
DOI: 10.1021/acsnano.9b07733
|View full text |Cite
|
Sign up to set email alerts
|

Delivery, Fate, and Mobility of Silver Nanoparticles in Citrus Trees

Abstract: Crop disease control is crucial for the sustainable development of agriculture, with recent advances in nanotechnology offering a promising solution to this pressing problem. However, the efficacy of nanoparticle (NP) delivery methods has not been fully explored, and knowledge regarding the fate and mobility of NPs within trees is still largely unknown. In this study, we evaluate the efficiency of NP delivery methods and investigate the mobility and distribution of NPs with different surface coatings (citrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 106 publications
4
53
0
Order By: Relevance
“…'Tree Tech ® OTC' is an oxytetracycline calcium complex registered for use in crop-bearing peaches and pears for bacterial blast, blossom blight, and fire blight management, and X-disease of peaches; however, there are few other bactericides registered for injection in crop-bearing trees. Oxytetracycline Effective [136,161] Most recently, injection experiments have extended beyond fungicides, insecticides, and bactericides to include other compounds such as plant defense activators [114,161,174], RNA [28,175], plant growth regulators [176], nanoparticles [177][178][179], novel antimicrobial molecules [180], essential oils [181], biofertilizers [182], nutrients [183], nano-carrier treatments [97], and bacteria [157,[184][185][186]. However, none are currently used on a commercial basis.…”
Section: Bacterial and Phytoplasma Diseasesmentioning
confidence: 99%
“…'Tree Tech ® OTC' is an oxytetracycline calcium complex registered for use in crop-bearing peaches and pears for bacterial blast, blossom blight, and fire blight management, and X-disease of peaches; however, there are few other bactericides registered for injection in crop-bearing trees. Oxytetracycline Effective [136,161] Most recently, injection experiments have extended beyond fungicides, insecticides, and bactericides to include other compounds such as plant defense activators [114,161,174], RNA [28,175], plant growth regulators [176], nanoparticles [177][178][179], novel antimicrobial molecules [180], essential oils [181], biofertilizers [182], nutrients [183], nano-carrier treatments [97], and bacteria [157,[184][185][186]. However, none are currently used on a commercial basis.…”
Section: Bacterial and Phytoplasma Diseasesmentioning
confidence: 99%
“…It shows that the uptake of NMs is highly dependent on the type of delivery method used. In this context, Su et al investigated the fate and mobility of surface-modified AgNP delivery to trees by employing various methods, including direct tree injection and petiole feeding in Mexican lime citrus trees (Su et al, 2020). Further explanation of uptake and transport in conjunction with the fate and transformation of NMs is comprehensively reviewed by different groups (Lv et al, 2019;Su et al, 2019).…”
Section: Anatomical Difference and Mode Of Application-related Np Uptakementioning
confidence: 99%
“…Moreover, the NPs surface charge can be improved by coating, which contributes to their translocation [ 37 ]. Recent reports found that the material of surface coating can prevent the closure of stomata by decreasing the indiscriminate gathering of NPs, thus enhancing the absorption of NPs in crops [ 38 ]. Moreover, the utilization of functional groups and surfactants improves the bioavailability of NPs by increasing the NPs adhesion on the surface of leaves [ 39 , 40 ].…”
Section: Special Properties and Surface Modifications Of Npsmentioning
confidence: 99%